Special edition using Microsoft Office Excel 2007 - Jelen, Bill (Que, 2006)
Special Edition Using Microsoft Office Excel 2007 will ease the upgrade path to the lastest version of Microsoft best-selling spreadsheet program. The author, "Mr. Excel " introduces you to the new interface, allowing you to quickly get back up-to-speed in performing your job, and will then introduce the powerful new features available in Excel 2007. Among other skills, you will learn how to create amazing data visualizations using conditional formatting and in-cell data bars. This is the only book you need on Microsoft Office Excel 2007! " Excel 2007 is the biggest, most exciting release of Excel ever. This book's straightforward approach explains the most important features of Excel 2007 in a thorough, easy-to-understand format. Further, it clearly compares older versions of Excel with Excel 2007, which makes for a seamless transition to this newest version of the program. It is a must-have desk reference for today's business professional."--David Gainer, Group Program Manager, Microsoft Excel THE ONLY EXCEL BOOK YOU NEED We crafted this book to grow with you, providing the reference material you need as you move toward Excel proficiency and use of more advanced features. If you buy only one book on Excel, Special Edition Using Microsoft® Office Excel® 2007 is the book you need. Does your life play out in a spreadsheet? Do numbers in columns and rows make or break you in the work world? Tired of having numbers kicked in your face by other Excel power users who make your modest spreadsheets look paltry compared to their fancy charts and pivot tables? If you answered yes to any of these questions, Special Edition Using Microsoft® Office Excel® 2007 is the bookthat will make it all better. Learn quickly and efficientlyfrom a true Excel master using the tried and true SpecialEdition Using formula for success. Here, you'll findinformation that's undocumented elsewhere-even inMicrosoft's own Help systems. You'll learn from finelycrafted, real-life examples built by an author who livesand dies by the integrity of his spreadsheets. Excel's backbone is its formulas and functions. Master those and you will master your spreadsheets. Special Edition Using Microsoft Office® Excel® 2007 provides more down and dirty help with your formulas and functions than you'll find in any other book! See how it's done in real life! Don't settle for lame pivot table and chart examples found in other books ... This book provides beautifully detailed examples that not ...